EDUCATIONAL CONDITIONS FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCE AMONG BACHELOR’S STUDENTS IN VOCATIONAL EDUCATION THROUGH THE USE OF MULTIMEDIA TECHNOLOGIES - MYAHKOTA, Volodymyr (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2026)
The dynamic development of information and communication technologies necessitates updating the content and methods of professional training, orienting it toward digitalization, visualization of learning materials, and interactive forms of instruction. It has been established that multimedia technologies function not only as a means of information delivery but also as a tool for developing students’ professional thinking, cognitive abilities, and practical skills. The article substantiates the pedagogical conditions for the formation of professional competence of Bachelor’s degree students in vocational education (specialty 015.38 “Vocational Education (Transport)”) through the use of multimedia technologies. The pedagogical conditions are considered as a purposefully organized multimedia educational environment that integrates content, forms, methods, tools, pedagogical techniques, and modern digital learning technologies aimed at the effective development of future specialists’ professional knowledge, skills, and competencies. The following pedagogical conditions are identified: the creation of a multimedia educational environment in higher education institutions; the organization of continuous interaction between students and digital and interactive resources; the training of teachers in the use of multimedia technologies in professional practice; and the engagement of students in innovative activities within a multimedia environment. Further research prospects are related to improving methods for implementing multimedia technologies in professionally oriented disciplines and developing innovative educational models for training Bachelor’s degree students in vocational education under conditions of digital transformation.